The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4314/ajfand.v9i2.19223
|View full text |Cite
|
Sign up to set email alerts
|

Investment in cocoa production in Nigeria: A cost and return analysis of three cocoa production management systems in the Cross River State cocoa belt

Abstract: The study examined costs and returns in cocoa production in Cross River State by comparing three identified management systems of cocoa production in the area. A two-stage sampling procedure was used to select a hundred and fifty cocoa farmers for the study. Data used in the study were collected using structured questionnaires which were administered by the Agricultural Development Programme (ADP) extension agents using the participatory approach while the data were analysed using descriptive statistics such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 1 publication
4
24
0
Order By: Relevance
“…The least represented age group was 15-20 years' old which constituted only 6 percent of the total sample. The finding showed that the majority of the respondents were already in the productive age group and corroborates with past studies that also showed that youths in this age group tends to dominate agricultural activities (Adeogun, 2015;Nkang, Ajah, Abang and Edet, 2009). The result also show that half of the respondents were married (50%) followed by the singles (40%) divorced (6%) and the widows/widowers (4%).…”
Section: Results and Discussion Demographic Characteristics Of Resposupporting
confidence: 80%
“…The least represented age group was 15-20 years' old which constituted only 6 percent of the total sample. The finding showed that the majority of the respondents were already in the productive age group and corroborates with past studies that also showed that youths in this age group tends to dominate agricultural activities (Adeogun, 2015;Nkang, Ajah, Abang and Edet, 2009). The result also show that half of the respondents were married (50%) followed by the singles (40%) divorced (6%) and the widows/widowers (4%).…”
Section: Results and Discussion Demographic Characteristics Of Resposupporting
confidence: 80%
“…However, cocoa was abandoned for oil and this brought about a downslide of the cocoa economy. In recent years, the government has shifted attention to cocoa production, processing and marketing (Nkang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to employment, the cocoa sub-sector still offers quite a sizeable number of employments both directly and indirectly. In addition, cocoa is an important source of raw materials, as well as source of revenue to Governments of cocoa producing states (Nkang et al, 2009) The investment by cocoa farmers in new planting and replanting in Nigeria has been at low ebb. The objective of this paper is to assess the cocoa farmers' investment in cocoa planting and replanting…”
Section: Introductionmentioning
confidence: 99%